(untitled) (Mustansiria Dental Journal, 2005)
Asthma is a common inflammatory condition of lung airways. Its cause is incompletely understood . Patients with bronchial asthma are affected both by the disease and its treatment . The purpose of our study was to examine the salivary composition in asthmatic patients , and study the association between asthma and occurrence of selected oral symptoms . The study was divided into two phases. In the first phase (salivary analysis) the salivary composition and unstimulated salivary flow rates of 50 asthmatic patients were compared with that of 25 non -asthmatic subjects. In the second phase (questionnair survey) the occurrence of symptoms of oral diseases in asthmatics (n=I I3) was compared with that of non—asthmatic subjects (n=ll I .) In addition to the symptoms of oral diseases, data on background information were taken. The results of salivary analysis showed no statistically significant differences between the asthmatic and non- asthmatics concerning the salivary flow rate and composition, However, the asthmatic saliva samples showed lower potassium and higher inorganic phosphorus levels . In the questionnair survey , the subjects reported more symptoms (dry mouth ,sore mouth , halitosis , pain in Temporomandibular jiont (TMI) , stuffiness in (TMI) and clicking in (TMI) compaired to the controlled group. The presence of asthma precipitating factors and medication used had a considerable effect on the probability of having symptoms of oral diseases when compaired to non- users